2007
DOI: 10.1021/ma062502o
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Poly(ferrocenylsilanes) with Coumarin Side Groups and Their Photochemical Reactivity and Electrochemical Behavior

Abstract: Two novel photoreversible poly(ferrocenylsilanes) (PFS) with coumarin side groups, i.e., halfand whole-substituted poly(ferrocenyl(3-(7-hydroxycoumarin) propyl)methylsilane), are synthesized by transition metal-catalyzed ring-opening polymerization of ferrocenyl(3-chloropropyl) methylsilane monomer and subsequent group exchange and nucleophilic substitution reaction. The two polymers are characterized by elemental analysis, 1 H and 13 C NMR, FTIR, UV-vis, emission spectra, TG, and DSC. Their photochemical reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 33 publications
1
19
0
2
Order By: Relevance
“…This fact indicated that all electro‐active ferrocenyl moieties in 3a , 3b , and 3c possessed the same redox potential 27. Besides, the oxidation peak of copolymer shifted anodically, and the oxidation potential E pa of copolymer ascended, whereas the reduction potential E pc descended as the length of PAEFC side chain lowered 78. This result showed that the graft copolymers are more difficult to be oxidized, and the reversibility of electrode process becomes less while the content of PAEFC segment lifted.…”
Section: Resultsmentioning
confidence: 90%
“…This fact indicated that all electro‐active ferrocenyl moieties in 3a , 3b , and 3c possessed the same redox potential 27. Besides, the oxidation peak of copolymer shifted anodically, and the oxidation potential E pa of copolymer ascended, whereas the reduction potential E pc descended as the length of PAEFC side chain lowered 78. This result showed that the graft copolymers are more difficult to be oxidized, and the reversibility of electrode process becomes less while the content of PAEFC segment lifted.…”
Section: Resultsmentioning
confidence: 90%
“…This behavior can be attributed to the slower diffusion and therefore the lower rate of charge transfer in agreement with previous observations. 29…”
Section: Resultsmentioning
confidence: 99%
“…The former is a pep* transition attributed to electrons of the conjugated benzene nucleus and the later is related to the pep* transition of pyrone nucleus. 25 Fig. 12 showed the results of isopropanol gel of 11c before and after UV irradiation.…”
Section: Photoreactionmentioning
confidence: 99%